2015
DOI: 10.1245/s10434-015-4620-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Small Bowel Neuroendocrine Tumors: Specific Requirements and Their Impact on Staging and Prognosis

Abstract: Systematic palpation of the entire small bowel detects more multiple NETs than preoperative imaging. Systematic surgery with extensive LN resection is associated with low local recurrence. High CgA levels and carcinomatosis are linked with shorter survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 19 publications
3
71
0
Order By: Relevance
“…Surgical resection of the primary tumor with locoregional mesenteric lymph node dissection and metastasectomy, if feasible, is the only curative approach (16), although R0 resections have been reported to be feasible in only 20% of cases (17); however, it has been reported that the current rate is even higher (18).…”
Section: Locoregional Enterectomy With Lymph Node Dissectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Surgical resection of the primary tumor with locoregional mesenteric lymph node dissection and metastasectomy, if feasible, is the only curative approach (16), although R0 resections have been reported to be feasible in only 20% of cases (17); however, it has been reported that the current rate is even higher (18).…”
Section: Locoregional Enterectomy With Lymph Node Dissectionmentioning
confidence: 99%
“…However, technique standardization and specific guidelines for its role are still under debate (27). Whole small bowel (from Treitz ligand to the ileocecal valve) inspection and palpation with both hands is of great importance for pinpointing otherwise undetectable tumors (10,18). Preoperative CT-or MRI-angiography may be useful in determining the tumor and the lymph nodes sites in relation to the vessels, so that the optimal surgical resection is feasible, with adequate length of small bowel left behind (at least three jejunal arteries) in order to prevent short bowel syndrome (28,29).…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 3 more Smart Citations